Techno-Economic Analysis and Physicochemical Properties of Ceiba pentandra as Second-Generation Biodiesel Based on ASTM D6751 and EN 14214 - Jamaluddin, N.A.M.; Riayatsyah, Teuku Meurah Indra; Silitonga, Arridina Susan; Mofijur, M.; Shamsuddin, Abd Halim; Ong, Hwai Chyuan; Mahlia, Teuku Meurah Indra; Rahman, S.M. Ashrafur (MDPI, 2019)
Processing biodiesel from non-edible sources of feedstock seems to be thriving in recent years. It also has also gathered more attention than in the past, mainly because the biodiesel product is renewable and emits lower pollution compared to fossil fuels. Researchers have started their work on various kinds of biodiesel product, especially from a non-edible feedstock. Non-edible feedstocks such as Ceiba pentandra show great potential in the production of biodiesel, especially in the Southeast Asia region because the plants seem to be abundant in that region. Ceiba pentandra, also known as the Kapok tree, produces hundreds of pods with a length of 15 cm (5.9 in) and diameter 2-5 cm (1-2 in). The pods consist of seeds and fluffin the surrounding areas inside the pod, which itself contains yellowish fibre, a mixture of cellulose and lignin. The seeds of Ceiba pentandra can be used as feedstock for biodiesel production. The study for Ceiba pentandra will involve techno-economic, as well as a sensitivity analysis. Moreover, the study also shows that the techno-economic analysis of a biodiesel processing plant for 50 ktons Ceiba pentandra with a life span of 20 years is around $701 million with 3.7 years of the payback period. Besides that, this study also shows the differences in operating cost and oil conversion yield, which has the least impact on running cost. By improving the conversion processes continuously and by increasing the operational effciency, the cost of production will decrease. In addition, the study also explains the differences of final price biodiesel and diesel fossil fuel, both showing dissimilar scenarios subsidy and taxation. Biodiesel has a subsidy of $0.10/L and $0.18/L with a total tax exemption of 15%. The value was obtained from the latest subsidy cost and diesel in Malaysia. Finally, further research is needed in order to fully utilize the use of Ceiba pentandra as one of the non-edible sources of biodiesel. © 2019 by the authors.